Consequences of Economic Sanctions for Food Security of Russia - VORONIN, Boris; POTEKHIN, Nikolay; CHUPINA, Irina; SHARAPOVA, Valentina; KOT, Ekaterina; RAZORVIN, Ivan Vasilievich; MOKRONOSOV, Alexander; LYSENKO, Julia (Journal of Environmental Management and Tourism; Vol 9 No 8 (2018): JEMT Volume IX Issue 8(32) Winter 2018DO - 10.14505//jemt.v9.8(32).20, 2019)
Ensuring food security of the Russian Federation is one of the most important tasks of state and local government. The modern agro-food policy of the Russian state is focused on the development of agriculture, which is able to provide the population with staple foodstuffs in accordance with rational norms and medical indicators and with minimal imports of agricultural products. The practical implementation of the Food Security Doctrine has contributed to the revival of lost positions in the field of agriculture and more sustainable economic development of the whole agro-industrial complex of the country. How-ever, the economic sanctions imposed on the Russian Federation had a negative impact on the economy of the agrarian sector. At the same time, the counter-sanctions introduced by the Russian state contributed to the transition from imports to accelerated domestic production of agricultural products, raw materials and food. The article discusses the development of Russian agriculture in the context of economic sanctions and their impact on ensuring the country's food security. The problem of ensuring the country's food security includes well-thought-out systemic solutions, researches and the implementation of an effective long-term strategy for the development of food security. Among such solutions is the development of a system of measures to improve reproduction, personnel, tax, credit, price, investment, innovation policies and other areas.